Block of Voltage-Gated Sodium Channels by Aripiprazole in a State-Dependent Manner - Föhr, Karl Josef; Rapp, Michael; Fauler, Michael; Zimmer, Thomas; Jungwirth, Bettina; Messerer, David Alexander Christian (International Journal of Molecular Sciences, 2022)
Aripiprazole is an atypical antipsychotic drug, which is prescribed for many psychiatric diseases such as schizophrenia and mania in bipolar disorder. It primarily acts as an agonist of dopaminergic and other G-protein coupled receptors. So far, an interaction with ligand- or voltage-gated ion channels has been classified as weak. Meanwhile, we identified aripiprazole in a preliminary test as a potent blocker of voltage-gated sodium channels. Here, we present a detailed analysis about the interaction of aripiprazole with the dominant voltage-gated sodium channel of heart muscle (hNav1.5). Electrophysiological experiments were performed by means of the patch clamp technique at human heart muscle sodium channels (hNav1.5), heterologously expressed in human TsA cells. Aripiprazole inhibits the hNav1.5 channel in a state- but not use-dependent manner. The affinity for the resting state is weak with an extrapolated Kr of about 55 µM. By contrast, the interaction with the inactivated state is strong. The affinities for the fast and slow inactivated state are in the low micromolar range (0.5–1 µM). Kinetic studies indicate that block development for the inactivated state must be described with a fast (ms) and a slow (s) time constant. Even though the time constants differ by a factor of about 50, the resulting affinity constants were nearly identical (in the range of 0.5 µM). Besides this, aripirazole also interacts with the open state of the channel. Using an inactivation deficit mutant, an affinity of about 1 µM was estimated. In summary, aripiprazole inhibits voltage-gated sodium channels at low micromolar concentrations. This property might add to its possible anticancer and neuroprotective properties.
CRIS-Team Scopus Importer:2022-11-25
Keywords: aripiprazole; cardiotoxicity; electrophysiology; patch clamp; sodium channel